PENANGANAN IKAN HASIL TANGKAPAN PADA KMN. DUA PUTRI 02 DI PELABUHAN PERIKANAN SAMUDERA (PPS) KENDARI, SULAWESI TENGGARA - Rakhma Fitria Larasati; Ambrosius Dominikus Basa Bay Bay; Hawati Hawati; Angkasa Putra; Sarifah Aini; Rahmatang Rahmatang (Universitas Mataram, 2024)
The two phases of handling fish catches include on-board handling and landing/unloading processes. Through this approach, the quality of catches can be maintained along the fishery supply chain, from ships to consumers, which contributes to the sustainability of the fishing industry as well as the provision of quality fishery products. This study aimed to analyze the process of fish handling in KMN. Dua Putri 02 and Fish Auction Site (TPI). The study was conducted from November 3, 2023, to December 29, 2023, at PPS Kendari, Southeast Sulawesi. The results of this study provided in-depth insight into the process of handling fish in both locations. On KMN. Dua Putri 02, the process began with the preparation of tools, the removal of fish from the net to the hold, and the application of ice to the hatch. At TPI, the process started with the preparation of tools for unloading, the transfer of fish from the hold to the sorting place, sorting by type, size, and physical shape, and then weighing and distributing the fish to the point of sale or auction of fish. The conclusion of this study provided a comprehensive overview of the flow of fish handling from vessels to TPI, offering a basis for improving efficiency and quality in the fishing industry.